2017
DOI: 10.1103/physrevphyseducres.13.010125
|View full text |Cite
|
Sign up to set email alerts
|

Using the resources framework to design, assess, and refine interventions on pressure in fluids

Abstract: The resources framework provides a useful and generative model of student thinking and learning. In particular, it suggests various strategies for instruction such as priming resources and refining intuition that allow students to build on knowledge they already have. In this paper, we describe the affordances of the resources framework in guiding the design, assessment, and refinement of interventions on pressure in fluids. This perspective kept us alert for cognitive resources on which students could build a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
1
16
0
3
Order By: Relevance
“…In fluid mechanics, literature on teaching, formative assessment, remedial instruction, and tools are expanding much more than excepted. It has been reported that concepts from pressure and fluid statics [57,[60][61][62][63][64][65], to Archimedes' principle [66], to Bernoulli's law often lead to misunderstandings [67][68][69][70][71][72]. To combat such misconceptions, various studies have developed approaches such as CFD instrumentation, e-learning, experimental hands-on implementation, interview analyses, student engagement, and interactive learning techniques, among others [73][74][75][76][77][78][79][80].…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicsmentioning
confidence: 99%
“…In fluid mechanics, literature on teaching, formative assessment, remedial instruction, and tools are expanding much more than excepted. It has been reported that concepts from pressure and fluid statics [57,[60][61][62][63][64][65], to Archimedes' principle [66], to Bernoulli's law often lead to misunderstandings [67][68][69][70][71][72]. To combat such misconceptions, various studies have developed approaches such as CFD instrumentation, e-learning, experimental hands-on implementation, interview analyses, student engagement, and interactive learning techniques, among others [73][74][75][76][77][78][79][80].…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicsmentioning
confidence: 99%
“…Perlu dilakukan penelitian tentang strategi pembelajaran yang cocok untuk meningkatkan keterampilan berpikir kritis tanpa mengabaikan esensi dari materi pembelajaran yang sedang dipelajari sehingga domain umum dan khusus dari berpikir kritis tetap diperoleh siswa. Strategi pembelajaran ini dapat berupa model pembelajaran yang dapat memfasilitasi siswa untuk belajar secara aktif (Lasry, Charles, & Whittaker, 2014) dan dapat membangun konsep yang benar (Young, College, & Peter, 2017) sehingga didapatkan hasil belajar yang baik (Merrill, 2013 ;Dawit Tibebu Tiruneh et al, 2016).…”
Section: Pendahuluanunclassified
“…While previous research primarily focused on identifying student difficulties or misconceptions, a few studies have taken a resources lens, seeking to identify "seeds of science" in student ideas, which rather than needing to be replaced, may be nurtured by instruction and grown into canonically correct physics concepts [19][20][21]. These studies have identified students' conceptual resources about heat and temperature, including that heat transfer is directional, that temperature is associated with energy, and that systems naturally move 'toward' equilibrium [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%